STUDENT PERCEPTION OF POLITENESS ETIQUETTE IN COMMUNICATING THE LEARNING PROCESS PKn - Yuafiyaka Fika; Adelina Hasyim; Yunisca Nurmalisa (FKIP Unila, 2012)
The purpose of this study was to analyze the students' perceptions of politeness etiquette in communicating with students and student teachers with students during the learning process Civics. The method used in this research is descriptive qualitative method with a population of 35 students. Data analysis using the percentage. Based on the analysis of the data it can be seen that the students' perceptions of politeness etiquette in communicating the learning process from the Marketing Civics class XI students with teacher indicators have unfavorable category. While the indicators of students with students having no good category. And based on the analysis of the overall data have unfavorable category, This shows that the civilized politeness in communication are at levels less good at learning civics class XI SMK PGRI 1 Marketing in Central Lampung Punggur Academic Year 2012/2013. Keywords: Linguistic Politeness, Communications.